Rapid Isolation of Functional ex vivo Human Skin Tissue-Resident Memory T Lymphocytes - Du, Weijie; Lenz, Daniel; Köhler, Ralf; Zhang, Erping; Cendon, Carla; Li, Jinchan; Massoud, Mona; Wachtlin, Joachim; Bodo, Juliane; Hauser, Anja E.; Radbruch, Andreas; Dong, Jun (Frontiers in Immunology, 2021)
Studies in animal models have shown that skin tissue-resident memory T (TRM) cells provide enhanced and immediate effector function at the site of infection. However, analyses of skin TRM cells in humans have been hindered by the lack of an optimized isolation protocol. Here, we present a combinatorial strategy- the 6-hour collagenase IV digestion and gentle tissue dissociation, for rapid and efficient isolation of skin TRM cells with skin tissue-specific immune features. In comparison with paired blood circulating memory T cells, these ex vivo isolated skin T cells express typical TRM cell markers and display higher polyfunctional properties. Moreover, these isolated cells can also be assessed for longer periods of time in ex vivo cultures. Thus, the optimized isolation protocol provides a valuable tool for further understanding of human skin TRM cells, especially for direct comparison with paired peripheral blood T cells at the same sample collection time.